Bamboo for Sustainable Livelihood in India - Singh, Ombir (Indian Forester, 2008)
The bamboo sector to serve as an eco-friendly source of goods & services and livelihood to millions of people in India including the challenges and efforts to be undertaken in this direction has been discussed in detail in this paper.